Students’ Perceptions on the use of Technology in Language Teaching - Ngcobo, Sandiso (Journal of Education and Vocational Research, 2014)
Research on the use of technology in educational settings has tended to focus on the impact of technology on the educational outcomes. The other area that that has long been ignored in this research field, when it should form an integral part of research in educational technology, is historical background and views of the students on the technology’s role in achieving educational goals. The research theory that is relevant in this regard is cultural-historical activity theory (CHAT) to additional language learning in education that is drawn from the cultural-historical psychology theory. One-hundred and five participants completed a survey questionnaire. The findings reveal that 66% of the respondents come from families where there are no computers at home and 57% have no good knowledge of computer use even though 53% claim to have been introduced to the use of computers at their last schools. Despite this, the respondents show overwhelming support for the use of technology in higher education. The results are important in that they give hope on the acceptance and possible independent use of technology by students to improve their English proficiency once they have been introduced to technology in language learning.